Influence of the microhabitat on water quality indexes in a montano forest stream, Junín, Peru - Sajamí Reymundo, Janet Isabel (2021)
Aquatic macroinvertebrates are widely used in environmental studies, mainly in bioindication, where their use depends on the knowledge of this community. The objective of the present study was to determine the influence of the microhabitat on two of the most used indices to evaluate the water quality BMWP / Col and ABI, for which four microhabitats were evaluated (stone, gravel, moss and leaf retained in the stream) collecting a total of 103 genera distributed in 52 families of aquatic macroinvertebrates. Of the four microhabitats evaluated, leaf registered the greatest richness and abundance (90 genera and 5 069 individuals). The results showed that the different microhabitats had a significant effect on the bioindication metrics BMWP/Col and ABI (p <0.05), and multiple post hoc comparisons showed significant differences (p <0.05) between the stone-leaf microhabitats. and moss-leaf highlighting the importance of multi-habitat sampling. It was concluded that both the BMWP/Col and ABI index depend on the heterogeneity of the habitat and the use of both would complement each other to determine the aquatic quality in streams of a montane ecosystem.